Human participation approach to organisations' foresight systems : identifying elements that support or impede organisation members’ participation in organisational foresight - Halkilahti, Maria (My University, 2021)
Strategic foresight helps organisations prepare for the future and seize the opportunities in the fast-changing operational environment. Foresight is, by definition, participatory activity and can be used, for example, as a management technique. Interest in participatory decision-making has increased in recent years. Accordingly, in strategic foresight literature, the needs to better understand how organisation members’ participation in foresight should be organised and what is the value participation could generate. This study examines human participation in organisational foresight, a concept that refers to strategic foresight practised in an organisational context. Participation includes organisation members’ participation in organised foresight activities and informal future-oriented discussions and actions, and utilisation of foresight thinking, methods, and tools. In this study, participation is examined from the intersection of foresight system, organisational characteristics and individual organisation members. This study aims to identify elements in the foresight system and organisational context that support or impede participation. The theoretical framework of this thesis draws on organisational foresight, participation in foresight and foresight systems. This study examined three frameworks, The Maturity Model of Corporate Foresight (Rohrbeck 2011), Certified Foresight Professional -programme’s Foresight System Framework and a systems view of foresight (Dufva 2015) to build an understanding of the systems’ essential elements related to participation. All seven informants were Certified Foresight Professional programme -alumni and represented different organisations. The empirical data was acquired by a questionnaire and interviews and analysed using the pragmatic iterative approach by Tracy (2013). The results of the study indicate that supportive elements for human participation in organisational foresight include: integration of organisational processes, clear responsibilities and expectations related to foresight, implementation or educational processes that equip and motivate organisation members to contribute to foresight, organisation members’ possibilities to impact on their work and develop their capabilities, and promoting benefits of foresight. Imbedding elements are related to, e.g.lack of systematic processes, lack of shared aims for participation and lack of time for foresight.

Strateginen ennakointi auttaa organisaatioita valmistautumaan tulevaisuuteen ja tarttumaan mahdollisuuksiin, joita toimintaympäristön nopeat muutokset tuovat esiin. Ennakointi on määritelmällisesti osallistavaa ja sitä voidaan hyödyntää esimerkiksi johtamismenetelmänä. Kiinnostus osallistavaan päätöksentekoon on ollut kasvussa viime vuosina. Strategisen ennakoinnin kentällä on ilmaistu myös tarve ymmärtää paremmin, miten organisaatioiden ennakointi pitäisi järjestää ja millaista lisäarvoa osallistavuus tuottaa. Tässä tutkimuksessa tarkastellaan ihmisten osallistumista organisaatioiden ennakointiin. Käsitettä käytetään tässä tutkimuksessa organisaatioissa hyödynnettävän strategisen ennakoinnin synonyyminä. Osallistumiseksi lasketaan organisaation jäsenten osallistuminen sekä järjestettyyn ennakointitoimintaan että epämuodollisiin tulevaisuuteen suuntaaviin keskusteluihin, ja toiminta, jossa yksilö hyödyntää ennakointiajattelua, menetelmiä ja työvälineitä omassa työskentelyssään. Tässä tutkimuksessa osallistumista tarkastellaan ennakointijärjestelmän, organisaation ominaispiirteiden ja yksilön leikkauspisteestä ja pyritään löytämään sekä ennakointijärjestelmästä että organisaation tasolta tekijöitä, jotka joko tukevat tai haittaavat organisaation jäsenten osallistumista ennakointiin. Tutkielman teoreettinen viitekehys koostuu organisaatioiden ennakoinnista, ennakoinnin osallistavuudesta ja ennakointijärjestelmästä. Lähemmässä tarkastelussa oli kolme ennakointijärjestelmämallia, Rohrbeckin (2011) organisaation ennakoinnin kypsyysmalli, Certified Foresight Professional (CFP) -ohjelman ennakointijärjestelmämalli ja systeeminen näkökulma (Dufva 2015). Nämä auttoivat muodostamaan käsityksen ennakkojärjestelmien osatekijöistä, jotka liittyvät osallistavuuteen. Tutkielman kaikki haastateltavat olivat suorittaneet CFP-ohjelman ja työskentelivät eri organisaatioissa. Tutkimuksen empiirinen aineisto kerättiin kyselyllä ja haastatteluilla ja analysoitiin Tracyn (2013) muotoilemalla laadullisen sisällön analyysin menetelmällä. Tutkimuksen tulokset osoittavat, että ihmisten ennakointiin osallistumista tukevat elementit liittyvät organisaatiokulttuuriin ja organisaation eri prosessien integroimiseen, ennakointiin liittyviin odotuksiin ja vastuunjakoon, ennakoinnin toimeenpanoon ja koulutusprosesseihin, motivaatiotekijöihin, organisaation jäsenten mahdollisuuksiin osallistua ennakointiin, organisaation jäsenten mahdollisuuksiin vaikuttaa työhönsä ja kehittää osaamistaan, sekä ennakoinnin hyötyjen viestimiseen osallistujille. Osallistumista haittaavat tekijät liittyvät esim. systemaattisten prosessien puutteeseen, osallistumisen tavoitteiden epäselvyyteen sekä liian vähäiseen ennakointiin käytettävissä olevaan aikaan. Ennakointijärjestelmän toimeenpano ja osallistumiseen liittyvien toimintamallien juurruttaminen ottaa aikansa. Organisaatiot, jotka tavoittelevat osallistumiseen perustuvia ennakointiprosesseja tai ennakointikulttuuria, saattaisivat hyötyä viitekehyksestä. Tämä tutkimus esittelee yksinkertaisen viitekehyksen, jossa yhdistyvät osallistumista tukevat ja haittaavat elementit.
Keywords: futures studies, foresight system, strategic foresight, participation, collaborative development, organisations, organising